The Court; Insulating Itself from Politics through the Doctrine of Political Questions: A Critical Exposition - A. Aziz, Shamrahayu (2012)
One of the most controversial theories in constitutional discourse is the doctrine of political questions. The court, by this, seeks to insulate itself from political pressures by avoiding the determination of questions which appear political in nature. The singular reason for this act is basically that some questions, such as this, are outside the purview of the courts to decide. Courts are therefore enjoined to refuse the determination of political questions in order to insulate itself from politics. This is despite the fact that democracy enjoins, constitutionalism, free speech, accountability, transparency, human rights, political pluralism and so on on the part of governmental institutions. The institution in which these concepts are anchored is the court. The paper therefore makes a critical exposition of the doctrine of political questions and contends that the court cannot insulate itself from politics merely because it has avoided the determination of political questions. Rather, this will amount to court abdicating its constitutional role as an organ of government. In this paper, various theories on political questions are examined. Keywords: Judiciary, Political Questions, Constitutionalism, Policy, Democrac